2022
DOI: 10.3390/w14050801
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of Low-Flow Changes in Lowland Rivers

Abstract: At the beginning of the 21st century, ongoing climate change led to research into extreme streamflow phenomena. This study aimed to assess the patterns of low-flow changes in different hydrological regions of Lithuania using selected hydrological indices (the annual minimum 30-day flow (m3 s−1) of the warm period—30Q), its duration, and deficit volume (below the 80th and 95th percentile flow: 30Q80 and 30Q95). Differences in low-flow indices in separate hydrological regions and over different periods (1961–202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Šarauskien ė et al [43] found that the intermittency of rivers in the surplus water zone is also related to atmospheric circulation and that intermittency processes are associated with the SCA index. Nazarenko et al [44] claimed that the effects of climate change are noticeable in discharges in the western and central parts of Lithuania during low flow periods. The application of the HBV model has shown that climate change will affect low flow indicators, including the multiannual minimum and average of low flow, and that the impact will vary depending on the feeding source of the rivers [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Šarauskien ė et al [43] found that the intermittency of rivers in the surplus water zone is also related to atmospheric circulation and that intermittency processes are associated with the SCA index. Nazarenko et al [44] claimed that the effects of climate change are noticeable in discharges in the western and central parts of Lithuania during low flow periods. The application of the HBV model has shown that climate change will affect low flow indicators, including the multiannual minimum and average of low flow, and that the impact will vary depending on the feeding source of the rivers [45].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the low flow and e-flow are linked in that ecological considerations should also be made during low flow and ensure that rivers maintain their ecological and environmental functions, even when the flow is reduced [47,48]. Short-term stressful low flows in Lithuania typically occur in late summer or early autumn [44]. All these findings call into question the current ecological flow regulation, which requires water users (primarily hydropower plant operators) to maintain a water flow equal to the multiannual mean of the average minimum discharge of 30 continuous days (Q 30 ).…”
Section: Introductionmentioning
confidence: 99%